2016
DOI: 10.1007/s40519-016-0267-7
|View full text |Cite
|
Sign up to set email alerts
|

How can the recall of early affiliative memories with peers influence on disordered eating behaviours?

Abstract: The present study aimed to explore the role of early affiliative memories with peers on the adoption of disordered eating attitudes and behaviours through the mechanisms of external shame and self-judgment. The sample used in the current study comprised 632 women from the community, aged between 18 and 60 years old.The tested model explained 22% of eating psychopathology's variance and showed excellent model fit indices. Results indicated that the impact of the recall of early positive memories with peers on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
(36 reference statements)
1
3
0
Order By: Relevance
“…In accordance with the proposed hypotheses and with prior research, the results of correlation analyses showed that early memories of warmth and safeness (both with family figures and with peers) were significantly associated with adaptive emotions and processes, and with lower eating psychopathology's severity (e.g., Ferreira et al, 2016;Mendes et al, 2016;Richter et al, 2009). Particularly, the current study extends current knowledge by demonstrating that the recall of positive emotional experiences is significantly associated with individuals' sense of safeness and connectedness to others, and with a positive attitude towards one's body, regardless of its characteristics.…”
Section: Discussionsupporting
confidence: 86%
“…In accordance with the proposed hypotheses and with prior research, the results of correlation analyses showed that early memories of warmth and safeness (both with family figures and with peers) were significantly associated with adaptive emotions and processes, and with lower eating psychopathology's severity (e.g., Ferreira et al, 2016;Mendes et al, 2016;Richter et al, 2009). Particularly, the current study extends current knowledge by demonstrating that the recall of positive emotional experiences is significantly associated with individuals' sense of safeness and connectedness to others, and with a positive attitude towards one's body, regardless of its characteristics.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, this study was built on previous research [34] to further clarify mechanisms that underlie the association between memories of warmth and connectedness and disordered eating. More specifically, the current study aims to complement previous research [34] emotional defensive responses (such as external shame) [35] and with eating psychopathological symptoms [36]. Moreover, results corroborate that external shame and unfavourable appearance-focused social comparisons are important correlates of disordered eating attitudes and behaviours [36,37].…”
Section: Path Analysismentioning
confidence: 99%
“…Therefore, a model of disordered eating wherein low perceived social rank is associated with disordered eating among vulnerable individuals through increased shame may explain why shame has been found to mediate the relationship between bullying and disordered eating in adolescent females ( Duarte et al, 2015 , 2017 ). This model may also explain why both shame (i.e., the perception that others evaluate you negatively) and self-criticism have been found to mediate the association between lack of affiliative memories with peers and disordered eating ( Mendes et al, 2017 ). To our knowledge, no studies to date have examined the role of shame in explaining the relationship between RB and disordered eating.…”
Section: Introductionmentioning
confidence: 99%